Immune Responses in Oral Papillomavirus Clearance in the MmuPV1 Mouse Model - Sarah A. Brendle; Jingwei J. Li; Vonn Walter; Todd D. Schell; Michael Kozak; Karla K. Balogh; Song Lu; Neil D. Christensen; Yusheng Zhu; Karam El-Bayoumy; Jiafen Hu (Pathogens, 2023)
Human papillomavirus (HPV)-induced oropharyngeal cancer now exceeds HPV-induced cervical cancer, with a noticeable sex bias. Although it is well established that women have a more proficient immune system, it remains unclear whether immune control of oral papillomavirus infections differs between sexes. In the current study, we use genetically modified mice to target CCR2 and Stat1 pathways, with the aim of investigating the role of both innate and adaptive immune responses in clearing oral papillomavirus, using our established papillomavirus (MmuPV1) infection model. Persistent oral MmuPV1 infection was detected in Rag1ko mice with T and B cell deficiencies. Meanwhile, other tested mice were susceptible to MmuPV1 infections but were able to clear the virus. We found sex differences in key myeloid cells, including macrophages, neutrophils, and dendritic cells in the infected tongues of wild type and Stat1ko mice but these differences were not observed in CCR2ko mice. Intriguingly, we also observed a sex difference in anti-MmuPV1 E4 antibody levels, especially for two IgG isotypes: IgG2b and IgG3. However, we found comparable numbers of interferon-gamma-producing CD8 T cells stimulated by E6 and E7 in both sexes. These findings suggest that males and females may use different components of innate and adaptive immune responses to control papillomavirus infections in the MmuPV1 mouse model. The observed sex difference in immune responses, especially in myeloid cells including dendritic cell (DC) subsets, may have potential diagnostic and prognostic values for HPV-associated oropharyngeal cancer.